An Audiovisual Introduction to Streamer Physics - Christoph Köhn (Atmosphere)
Streamers are small, thin plasma channels that form the precursors of hot lightning leaders and that are associated with phenomena such as transient luminous events or terrestrial gamma-ray flashes. We provide an easily accessible audiovisual introduction for students and early researchers, serving as a supplement to traditional review papers. This overview contains an introduction to the collision-dominated motion of electrons in an ambient field and an ambient gas, including a discussion of cross-sections and friction force. Based on this, we will discuss electron avalanches before moving to streamers. Here, we will focus on the avalanche-to-streamer transition and present properties and different modeling approaches. Finally, we will discuss streamers in different gas mixtures as well as their relation to lightning and plasma chemistry. The viewer of the supplementary video will receive a first overview of streamer physics.